Vitamin Drug conjugate: a systematic review of pharmacological potential - Bhole, R.P.; Shinde, Yogita; Bonde, C.G.; Wavhale, R.D. (KU Publ., 2021)
Cancer is a chronic disease which can cause death. In traditional chemotherapy cytotoxic drugs are used to kill proliferating cancer cells. The cytotoxic agent exhibits less specificity, less biological activity, causes systemic toxicity and undesirable side effects. Each year, about 1.8 million of the population are infected and die due to tuberculosis infection. An increase of drug resistance during the tuberculosis treatment is a significant concern. So, it is necessary to develop a new approach or therapies to resolve drug resistance, drug selectivity in tuberculosis infection and the reduction of the side effects of cytotoxic agents and anti-tubercular drugs. This review describes the newly emerging concept of «vitamin drug conjugate». Vitamin-drug conjugate is a specifically carried drug toward the target site, is one of the promising ways to treat chronic diseases like cancer and tuberculosis and enhance the therapeutic outcome. The purpose of this review is to explore vitamin as a targeting moiety for new anticancer and anti-tubercular drug to overcome challenges, such as nonselectivity, systemic toxicity and multidrug resistance. This approach is beneficial in the treatment of lifethreatening disease like cancer, tuberculosis and also in many viral infections.
Дәруменді дәрілік конъюгат: фармакологиялық потенциалын жүйелі түрде талдау
Конъюгат витамин – лекарственный препарат: систематический обзор фармакологического потенциала
Keywords: Cancer; Tuberculosis; Vitamin-Drug conjugate; Vitamin B12 conjugat; Folic acid conjugate; Biotin conjugate; Vitamin-E conjugate; Lipid drug conjugate